THE WARI OCCUPATION IN THE VALLEYS OF PALPA, PERU SOUTH COAST - Isla Cuadrado, Johny (2014)
Recent research in the Palpa valleys, in the northern section of the Rio Grande of Nasca drainage, has revealed many archaeological evidences (settlements, funerary structures, diverse materials and remains of daily life). This evidence is shedding new light on the intensity and nature of the Wari occupation in the south coast of Peru. Excavations in many sites with evidence of Wari occupation in the coast, the Yunga Desertica, and the highlands, help us to understand the strong integration that existed amongst different ecological zones and the interest that motivated the Wari to occupy the Palpa and Nasca valleys. In this context, the evidence registered until now in the Palpa valleys indicated that the south coast, and specially the Rio Grande drainage, had an important role in the Wari strategy of expansion and control in the region, allowing the access to resources not existent in the Ayacucho area.